Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis STEM Menggunakan Miniatur Perahu Jambi Berbantuan Arduino pada Materi Usaha dan Energi - Mega Aulia; Haerul Pathoni; Jules Nurhatmi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to develop a STEM-based Student Worksheet (LKPD) using a miniature Jambi boat assisted by Arduino on the topic of work and energy and to determine its feasibility for use in physics learning. This research employed a Research and Development (R&D) approach using the 4D development model proposed by Thiagarajan, consisting of Define, Design, Develop, and Disseminate stages. However, the study was limited to the Develop stage. The product was validated by two material experts, two media experts, and one science teacher, while student responses were obtained through a limited trial involving students of SMP Negeri 11 Muaro Jambi. Data were collected using interview guides, validation sheets, teacher assessment sheets, and student response questionnaires. The data were analyzed descriptively using percentage-based feasibility criteria. The results showed that the average validation score from material experts increased from 93.75% in the first stage to 95.00% in the second stage. The average validation score from media experts increased from 86.65% to 94.15%. The teacher assessment obtained a score of 93.30%, while student responses reached 84.75%. These results indicate that the developed LKPD meets the criteria of being highly feasible for use in learning activities. The integration of STEM components through Arduino-assisted miniature Jambi boats provides contextual and meaningful learning experiences that help students understand work and energy concepts more effectively. Therefore, the developed LKPD is considered valid and suitable as a supporting teaching material in junior high school physics learning.